Interrnational Corporate Finance - Madura, Jeff (Australia: South-Weastern CENGAGE Learning, 2010)
International Corporate Finance, Tenth Edition, presumes an understanding of basic corporate finance. It is suitable for both undergraduate and master's level courses in international financial management. For master's course, the more challenging questions, problems, and cases in each chapter are recommended, along with special projects.
Includes Index.
rpm 11/09/13
Loans
Keywords: Corporate Finance; corporate finace - International